2019
DOI: 10.1111/mcn.12870
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific risk factors for child anaemia in Myanmar: Analysis from the Demographic and Health Survey 2015–2016

Abstract: Anaemia is prevalent among preschool‐aged children in Myanmar, but few epidemiological studies of anaemia at the national level were reported. Using data from the Myanmar Demographic and Health Survey 2015–2016, we examined risk factors for anaemia at household, maternal, and individual levels for children aged 6–23 months (n = 1,133) and 24–59 months (n = 2,393) separately. Survey design and sampling weights were adjusted for in multivariate regression analyses. The prevalence of anaemia was 77.2% in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
1
1
4
Order By: Relevance
“…The percentage of anemia is very high at the age interval 6 to 23 months which is in line with other study [ 35 ] and then the prevalence declines. At 6 to 23 months of age, the requirement for iron is high as the growth and development of the child peaks at this stage [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of anemia is very high at the age interval 6 to 23 months which is in line with other study [ 35 ] and then the prevalence declines. At 6 to 23 months of age, the requirement for iron is high as the growth and development of the child peaks at this stage [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy might be due to methodology including sampling and quality of sample collection in demographic health surveys. Another study report in Myanmar reported that 77.2% of the children aged 6–23 month had anemia which is higher than this study finding [ 40 ]. Genetic, ethnic, and geographical lifestyle factors may all interact and can contribute for the discrepancy.…”
Section: Discussioncontrasting
confidence: 73%
“…Sobre este último factor, se encontró que los niños menores de cinco años con acceso a servicios básicos incompletos tuvieron un OR de 2,7 (OR=2,72; IC 95%: 1,24-5,97), comparable con el estudio realizado por Kang et al (18) en un país del sudeste asiático, en el que encontró que no contar con fuentes de agua potable mejoradas generaba 1,4 veces mayor riesgo de que los niños puedan desarrollar anemia, además que se asoció con la alta probabilidad de padecer enteroparasitosis, otro factor muy asociado a la cronicidad de la anemia. (19,20) Rev Med Hered.…”
Section: Discussionunclassified